What rates of productivity growth would be required to offset the effects of population aging? A study of twenty industrialised countries - Frank T. Denton; Byron G. Spencer (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2017)
A shift in population distribution toward older ages is underway in industrialised countries throughout the world and will continue well into the future. We provide a framework for isolating the pure effects of population aging on per capita GDP, employ the framework in calculations for twenty OECD countries, and derive the rates of productivity growth required to offset those effects. We consider also some labour-related changes that might provide offsets, for comparison with productivity.
Keywords: J1; J11; O4; 330; population aging; productivity; industrialised countries; projections